Evaluasi Time Schedule Menggunakan Network Planning (Studi Kasus: Pada Proyek Pembangunan Gedung Rawat Inap Kelas III Tahap III Rumah Sakit Umum Daerah Bangkinang, Riau) - Moreno, Yenita; Ermiyati, Ermiyati; Pratama, Syurya Adi; Suprasman, Suprasman (Mahesa Research Institute, 2023)
Time Schedule is a detailed division of work duration on each project work. The problem in this study is the ineffectiveness of the duration of the work and the amount of work done is not in accordance with the planned duration. The purpose of the study was to evaluate the time schedule using the network planning method to determine the critical trajectory by using Microsoft Project 2016 software and to accelerate the duration of work from its original duration by using the acceleration method of adding labor, increasing working hours and accelerating the work shift method. The conclusion of time schedule evaluation using network planning is obtained as many as 50 work items which are included in the critical path. After accelerating with three acceleration methods, it was found that the results of accelerating the addition of manpower which cut the time by 3 days from the original duration, acceleration by adding 2 hours of work cut 7 working days and acceleration with the work shift method which cut the duration to 21 working days from the original duration. which is 206 working days, then of the three methods of acceleration the most effective is the shift method.